The development of interactive multimedia on thematic learning in grade V by the theme history of Indonesian Civilization - Putra, Arda Purnama; Ruminiati, Ruminiati; Al Atok, A.Rosyid (Journal of Social Sciences (COES&RJ-JSS), 2017)
The development goal this research is to produce an interactive multimedia on the theme of learning the history of Indonesian civilization which is valid, practical, effective, and attractive. This research is a research development by using a development model of Borg and Gall which has been modified. Development model consists of 8 steps: (1) Research and data collection, (2) Planning, (3) Development of draft product, (4) The early field tests, (5) Revise the test results, (6) field tests, (7) Completion of the product field test results, (8) Final Product. The instruments used in this research are a validation questionnaire, test questionnaire, interview, and evaluation test. Preliminary field testing results, the product gets a score of 4.6 which is included in the practicality of practical criteria and got a score of 4.6, including the attractiveness of the interesting criteria. Based on the main field testing, theproduct get a score of practicality 4.5 which is included in the criteria of attractiveness of the practical and get a score of 4.2 which is included in the criteria of interest, as well as get a score of 84.7 Effectiveness included in the criteria effectively. Overall analysis of data from the validation sheet materials experts, media experts, and users of this product is getting an average score of 4.1 which is included in the valid criteria with minor revisions.